V m and ζ-potential of Candida albicans corelate with biofilm formation - Matthew P Johnson; Mohammad T. Al Bataineh; Sreejisha P Sreedharan; Herbert F. Jelinek; Michael Pycraft Hughes (Scientific Reports)
Abstract Microbial biofilms are known to defend against the host’s immune system and provide resistant to antimicrobial medications. Biofilms can form on various human organ systems spanning the gastrointestinal, respiratory, cardiovascular, and urinary organ systems. Conditions caused by the yeast Candida albicans can range from irritating thrush, to systemic and life-threatening candidiasis. Initial contact between organism and surface is mediated electrically, with subsequent interactions developed biochemically. Since different cells have different electrical characteristics, we hypothesised that alteration in these properties may align with different strains’ propensity for biofilm formation. We used three strains of C. albicans with different tendencies for biofilm formation and filament phenotype (the most filamentous strain nrg1 Δ/Δ, the least filamentous ume6 Δ/Δ, and wildtype DK318), we investigated the passive electrical properties, membrane potential V m and ζ-potential at two conductivities. Results suggest V m and ζ-potential correlate with a cell’s ability to form biofilms, suggesting correlation between membrane potential, ζ-potential and biofilm formation. Understanding this relationship may suggest potential routes to future prevention of biofouling and biofilm-related illness.